ORGANIZATION COMMUNICATION: A CRITICAL DISCOURSE ANALYSIS OF THE INTER-INSTITUTIONAL AGREEMENT FOR ACADEMIC INTERNATIONAL COOPERATION - Coelho, Adriane Marie Salm; Braga, Ana Carolina (The ESPecialist, 2016)
Up to now, very few business genres have been described, there is a need to investigate more about the genres in this area (Salm, 2000). In order to contribute to this area of research, academic agreements for international cooperation from higher educational institutions were analyzed in order to make a critical study of this particular discourse. The analysis draws on principles of critical discourse analysis, Fairclough’s (1992) tri-dimensional model of Critical Discourse Analysis, Halliday’s (1994) Functional Grammar, Ramos’s (1965) ‘Redução Sociológica’ and genre studies (Meurer, 1998). Results have shown evidence of the power relation between discourse participants.